PENGARUH JUMLAH RAKAAT SHALAT DHUHA TERHADAP DETAK JANTUNG MAKSIMAL LANSIA MUSLIMAH DI UPTD. PELAYANAN SOSIAL LANJUT USIA BINJAI TAHUN 2023 - Hadid Fachriansyah Ansari; Elman Boy (Buletin Farmatera, 2026)
Abstract: Dhuha prayer is a physical activity with light-moderate intensity that can induce the activity of the parasympathetic nerve and suppress the activity of the sympathetic nerve through the release of alpha waves of the brain. The intensity of exercise or physical activity with heart rate has a linear relationship. This study aims to determine the effect of the number of prayers on the heart rate of elderly Muslim women in the 2023 Binjai Senior Social Service UPTD. This type of research is experimental in one group community on all elderly Muslim women aged 60-80 years at UPTD. Social Services for the Elderly. The sample will perform dhuha prayers of 2-8 rak'ahs, and after completing 2 rak'ahs, will be measured by heart rate using a pulse oximeter. The results of the Pearson Correlation test showed a significant influence or correlation between the number of rak'ahs of dhuha prayer on heart rate (p=0.76). The results of the one-way ANOVA test showed significant changes in heart rate in each number of rak'ahs of dhuha prayer with a p0.001 value. There is an influence of the number of rak'ahs of dhuha prayer on the heart rate of the elderly and meaningful changes in heart rate in each number of rak'ahs of dhuha prayer.